Reviewing the Role of BUMDES in Bogor Regency in Increasing Revenue - Amas Priatna, Isep; Hakim, Dedi Budiman; Syaukat, Yusman; Effendi, Jaenal (MIMBAR : Jurnal Sosial dan Pembangunan, 2023)
BUMDes was born to accelerate village development in the economic.This research was conducted in 2019–2020 on BUMDEs in the Bogor district. The first objective of this study, using panel data regression, is to find out how far the internal and external influences of the business increase the income of BUMDes. The second goal, using the Cobb-Douglas production function with the stochastic frontier and the MLE (maximum likelihood estimation) production function approach, is to determine the efficiency level of BUMDes fund management. The results of this study show that the number of workers as part of the internal business of BUMDes has a positive and significant influence on increasing the income of BUMDes. While the number of residents and stores that market the results of BUDes products also influences the external side of the business, The efficiency rate of BUMDes is 57%, with operational costs as the most critical variable.